2015
DOI: 10.1111/1744-9987.12292
|View full text |Cite|
|
Sign up to set email alerts
|

Two Years of Cinacalcet Hydrochloride Treatment Decreased Parathyroid Gland Volume and Serum Parathyroid Hormone Level in Hemodialysis Patients With Advanced Secondary Hyperparathyroidism

Abstract: The long-term effect of cinacalcet hydrochloride treatment on parathyroid gland (PTG) volume has been scarcely investigated in patients with moderate to advanced secondary hyperparathyroidism (SHPT). The present study was a prospective observational study to determine the effect of cinacalcet treatment on PTG volume and serum biochemical parameters in 60 patients with renal SHPT, already treated with intravenous vitamin D receptor activator (VDRA). Measurement of biochemical parameters and PTG volumes were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…In a very recent 2-year follow-up study of cinacalcet treatment in renal HPT patients, a maximal and total decrease of parathyroid gland volume by 30 % was found alongside significant decrease of serum PTH levels, calcium, and phosphate. However, 10 out of 60 patients revealed a 30 % increase of maximal parathyroid volume after 2 years [113] (EL 3). From these changes no essential effect on surgical procedure may be expected, except possible challenge in preoperative parathyroid gland localization in ultrasonography and intraoperative parathyroid gland identification.…”
Section: Surgery In Renal Hyperparathyroidism With and Without Continmentioning
confidence: 99%
“…In a very recent 2-year follow-up study of cinacalcet treatment in renal HPT patients, a maximal and total decrease of parathyroid gland volume by 30 % was found alongside significant decrease of serum PTH levels, calcium, and phosphate. However, 10 out of 60 patients revealed a 30 % increase of maximal parathyroid volume after 2 years [113] (EL 3). From these changes no essential effect on surgical procedure may be expected, except possible challenge in preoperative parathyroid gland localization in ultrasonography and intraoperative parathyroid gland identification.…”
Section: Surgery In Renal Hyperparathyroidism With and Without Continmentioning
confidence: 99%
“…We did not find any case reports or animal trials considering this issue. Only for secondary hyperparathyroidism in hemodialysis patients, adenoma growths as well as regression induced by cinacalcet are described [6]. However, since renal function was normal and serum Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The latter was seen only in areas with nodular hyperplasia [7]. Known molecular mechanisms mediating volume reduction of adenomas as well as regressive alterations are antiproliferative effects on the parathyroideal cells caused by calcium-sensing-receptor activation as well as induction of apoptosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…Rat models of SHPT demonstrated that cinacalcet attenuates the progression of parathyroid hyperplasia by reducing the number of parathyroid cells and decreasing the weight of the parathyroid (40). Yamada et al (41) reported that cinacalcet therapy combined with vitamin D analogues significantly decreased the volume of the parathyroid gland and PTH serum levels in hemodialysis patients with SHPT. These findings support the application of combination therapy to enable patients to achieve KDOQI targets (OR=3.51; 95% CI, 2.38-5.17) (37).…”
Section: Discussionmentioning
confidence: 99%